Pharmacokinetics of lenalidomide during high cut-off dialysis in a patient with multiple myeloma and renal failure - Dao, Kim (Cancer Chemother Pharmacol, 2016)
INTRODUCTION: High cut-off dialysis, increasingly used in multiple myeloma patients, is susceptible to influence anticancer drug elimination. We report about lenalidomide disposition in a patient on high cut-off dialysis for renal failure secondary to myeloma cast nephropathy. METHODS: The patient received a higher dosage of lenalidomide (5 mg b.i.d.), owing to concerns about a potential decrease in lenalidomide exposure during dialysis sessions. A set of blood samples was taken in order to develop a pharmacokinetic model accounting for lenalidomide concentrations in this setting. RESULTS: According to our model, the area under the curve was 3273 µg h/L, i.e., 60% higher than expected under usual dosage (25 mg q.d.) with normal renal function. Despite this, the patient did not develop major hematological toxicity. CONCLUSIONS: Lenalidomide doses of 5 mg b.i.d. led to high exposure in a patient with renal failure undergoing high cut-off dialysis. Yet, the dosage of 5 mg q.d. recommended in conventional dialysis would probably be adequate in such patients.